(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Modification and loss of forests due to natural and anthropogenic disturbances contribute an estimated 20% of annual greenhouse gas (GHG) emissions worldwide. Accounting GHG emissions associated with forestry, specifically, and land use generally is crucial in recent days because forests play major roles in balancing terrestrial carbon and contribute to the mitigation of global warming and climate change. Consequent to the awareness of climate change, reducing emission from deforestation and forest degradation, and conservation (REDD+) programmed was introduced at the international level to promote forest conservation and enhance forest governances. Intergovernmental Panel on Climate Change (IPCC) came out with protocols on how to account the carbon stored and released from the forests. Principally there are five primary carbon pools in a forest, which are above-ground biomass, below-ground biomass, deadwood, litter, and soils that accumulate and in some conditions release carbon. However, about 98% of carbon stored in a forest comprises trees components (aboveground and belowground living biomass, deadwood and litters) and the remaining is stored in soils. Many factors interact to affect the flux dynamics of these carbon pools, including the type of forest ecosystem, the age of the forest, and if harvested, the length of stand rotation cycles and the forestry practices used. Logging these forests, in a sense, represents an opportunity cost, as the time necessary for a harvested forest to regain its carbon sink capacity can take many decades, and if left undisturbed, would have gone on to expand its carbon pool or at least remain in constant over time. In this study, the lowland dipterocarp forest, where logging often takes place, is profiled in terms of biomass carbon. Pahang, which has the largest forest cover and biggest timber production in Peninsular Malaysia, was selected as the study area. The dipterocarp forests comprise both protection and production functions were categorized into strata based on year elapsed after logging (i.e. logged 1-10, 11-20, 21-30, and > 30 years). Measurements have been conducted on the ground and all the carbon pools in these strata were assessed. The study found significant differences between each stratum in terms of carbon and the results are presented in this paper. The effects of harvesting practices on carbon pools are also discussed.